Parental risk-taking behaviour and nest defence during the nestling rearing stage in Northern House Wrens Troglodytes aedon - Fernandez, Gustavo Javier (2013)
Risk-taking behaviour of short lived nesting birds is often explained in relation to the reproductive value of offspring (the reproductive value hypothesis) and the harm that the absence of parental care can cause to nestlings (risk of harm-to-offspring hypothesis). The reproductive value hypothesis predicts that the risk assumed by adults should increases with nestling age, whereas the risk of harm-to-offspring hypothesis predicts the opposite pattern. We assessed the risk-taking behaviour of nesting males and females Northern House Wrens, Troglodytes aedon, faced with a predation threat (plastic owl model) when rearing 3-4 and 10-12 days old nestlings. We used the time elapsed until parents first entered the nest-box as a measure of risk-taking behaviour and alarm calling rate as a proxy of nest defence. Females resumed sooner parental activities when exposed to the model when nestlings were young, supporting the risk of harm-to-offspring hypothesis. In contrast, the time lasted to resume parental duties by males did not differ between nestling ages. Alarm calling rate increased with the nestling stage, as predicted by the reproductive value hypothesis. We suggest that nesting House Wrens responded to both nestling requirements and to the reproductive value of thebrood, assuming greater risks when nestlings are more vulnerable and a more intense nest defence when nestlings are older.